Characterization of human alveolar macrophages and blood monocyte-derived macrophages responses to M.tb in TB close contacts with and without type 2 diabetes - Kunsevi Kilola, Carine (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.